Polyphenolic Profiling and Evaluation of Antioxidant, Antidiabetic, Anti-Alzheimer, and Antiglaucoma Activities of Allium kharputense and Anchusa azurea var. azurea - Tahiroglu, Veysel; Karagecili, Hasan; Aslan, Kubra; Gulcin, Ilhami (Mdpi, 2025)
The genera Allium (Liliaceae) and Anchusa (Boraginaceae) are flowering plant genera with a rich diversity, also including the Allium kharputense Freyn & Sint. and Anchusa azurea Mill. var. azurea species. The antioxidant, anti-Alzheimer's disease (AD), antidiabetic, and antiglaucoma effects of the Allium kharputense Freyn & Sint. and Anchusa azurea Mill. var. azurea species, which are commonly eaten foods in the Southeast of T & uuml;rkiye in the treatment of several diseases, were studied. To interpret the antioxidant capacities of ethanol extract of two plant species, aerial parts were analyzed by ABTS and DPPH assays. The IC50 values of A. kharputense and A. azurea ethanol and water extracts for ABTS center dot+ activities were recorded in the range of 30.93 to 33.94 mu g/mL and 33.45 to 33.78 mu g/mL, respectively. Also, DPPH center dot activities were measured at 30.78 to 36.87 mu g/mL and 31.67 to 32.45 mu g/mL, respectively. The best of the IC50 values was measured in the ethanol extract of A. kharputense as 30.78 mu g/mL for DPPH scavenging activity. The total phenolic and flavonoid quantities in A. kharputense and A. azurea plants were measured. The highest phenolic and flavonoid contents of A. kharputense and A. azurea species were recorded in amounts of 445.52 and 327.35 mg GAE/g in ethanol extracts, respectively, and 332.88 and 234.03 mg QE/g in ethanol extracts, respectively. The effects of A. kharputense and A. azurea on diabetes, AD, and glaucoma were studied on the target enzymes of diseases. The most efficient IC50 values were recorded at 10.72 mu g/mL against alpha-glycosidase, 35.01 mu g/mL against AChE, 38.05 mu g/mL against BChE, 9.21 mu g/mL towards hCA I, and 81.02 mu g/mL towards hCA II isoenzymes. The kinds and amounts of phenolic compounds in A. kharputense and A. azurea were determined using LC-MS/MS against 53 standards. A. kharputense and A. azurea plants have prospective use in enhancing glaucoma, diabetes, AD, Parkinson's disease, epilepsy, and cancerous disorders.
Keywords: Allium kharputense; Anchusa azurea; antioxidant; alpha-glycosidase; acetylcholinesterase; carbonic anhydrase; phenolic compounds